Strategi Pengembangan Lahan Perkebunan Kopi Desa Wonosalam Dusun Mangirejo Sebagai Camping Ground Dengan Konsep Ekowisata - Dhian Satria Y. K; Dani Firmansyah Pradana; Novarezta Rexlin; Wahyuni Maulida (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This study aims to determine the strategy for developing the natural tourism potential of Kebon Kopi tourism as a camping ground located in the Sumber Gogor area, Mangirejo Hamlet, Wonosalam Village, Jombang Regency. This research will use qualitative methods, observation, interviews, and literature study. The results of the study indicate that the supporting factors in the Kebon Kopi tourist attraction as a camping ground are very supportive for further development, while the deficiencies that exist need to be considered and handled seriously so as not to hinder the development of Kebon Kopi tourism as a camping ground. In addition, the strategy that needs to be carried out in developing Kebon Kopi tourism objects as camping grounds is the presence of new ideas and collaboration with the government, private sector, and academics.